A Mindfulness-Based Stress Reduction Program via Group Video Conferencing for Adults With Cerebral Palsy – A Pilot Study - Høye, Helene; Jahnsen, Reidun Birgitta; Løvstad, Marianne; Hartveit, Jeanette Folkvord; Sørli, Hilde; Tornås, Sveinung; Månum, Grethe (Frontiers in Neurology, 2020)
Purpose: Adults with cerebral palsy experience challenges related to lifelong disability, such as stress, fatigue, pain and emotional issues. E-health services can be delivered regardless of residence and level of functioning. The aim of this pilot study was to explore the potential benefits and feasibility of a mindfulness-based program delivered to adults with cerebral palsy via group video conferencing. Methods: Six adults with cerebral palsy received an eight-week mindfulness group-based program via video conferencing. A multiple single-case study design was applied, including quantitative and qualitative elements. Pain was assessed 16 times through the study period. Questionnaires were administered to gather data on pain catastrophizing, stress, fatigue, emotional distress, positive and negative affect, and quality of life. A focus group interview addressed experiences with the intervention and the mode of delivery. Results: The participants’ pain levels showed varied trajectories. Pain catastrophizing and negative affect were statistically significant decreased. Qualitative data indicated benefits from mindfulness in coping and stress management. The video conferencing delivery was evaluated as feasible, with no major adverse effects. Conclusion: Since the pilot study had a small sample size, potential treatment benefits should be interpreted with caution. However, this pilot study provides important information in the planning of future larger and controlled studies on mindfulness-based interventions programs via video conferencing for adults with cerebral palsy and other persons living with long-term disability.